Cost-effectiveness analysis of lurbinectedin plus atezolizumab as first-line treatment for extensive-stage small-cell lung cancer - Huang, Yufan; Xu, Zheqi; Bao, Leilei (Frontiers in Immunology, 2025)
BackgroundThe IMforte trial demonstrated that lurbinectedin combined with atezolizumab (LU-AT) as a first-line regimen offers clinical advantages over atezolizumab alone (AT) in patients with extensive-stage small-cell lung cancer (ES-SCLC). However, given the high costs of lurbinectedin and atezolizumab, the cost-effectiveness of LU-AT relative to AT remains uncertain. This study aims to assess the cost-effectiveness of LU-AT as a first-line treatment for ES-SCLC within the context of China’s and the United States’ healthcare system.MethodsA partitioned survival analysis (PartSA) model was employed to assess the cost-effectiveness of LU-AT as a first-line treatment for ES-SCLC. Clinical efficacy data were sourced from the IMforte trial. Drug costs were based on national tender prices, while other costs and utility values were derived from the literature. Outcomes included total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). One-way sensitivity analysis and probabilistic sensitivity analysis were conducted to assess the robustness of the model.ResultsThe combination regimen of lurbinectedin plus atezolizumab yielded an additional 0.21 QALYs compared with atezolizumab monotherapy, leading to an ICER of $374,167.43 per QALY in China and $1,071,237.82 per QALY in the USA, both beyond the willing-to-pay threshold ($40,365.00/QALY in China and $150,000.00/QALY in the USA). The utility of progression-free survival (PFS), the cost of lurbinectedin, body surface area (BSA), and the cost of atezolizumab are the four most influential factors in both China and the United States. Across all sensitivity analyses, the outcomes generated by the models remained robust. At a willingness-to-pay threshold of $40,365 and $150,000 per QALY, the probability of LU-AT being cost-effective relative to AT was 0% in China and USA.ConclusionWithin the framework of China’s and the United States’ healthcare system, LU-AT is unlikely to represent a cost-effective first-line treatment for ES-SCLC.